Aging‐Related Expression of Twinfilin‐1 Regulates Cholangiocyte Biological Response to Injury. Issue 3 (11th March 2019) - Maroni, Luca; Pinto, Claudio; Giordano, Debora Maria; Saccomanno, Stefania; Banales, Jesus M.; Spallacci, Daniele; Albertini, Maria Cristina; Orlando, Fiorenza; Provinciali, Mauro; Milkiewicz, Malgorzata; Melum, Espen; Labiano, Ibone; et al.
Abstract : Disorders of the biliary tree develop and progress differently according to patient age. It is currently not known whether the aging process affects the response to injury of cholangiocytes. The aim of this study was to identify molecular pathways associated with cholangiocyte aging and to determine their effects in the biological response to injury of biliary cells. A panel of microRNAs (miRs) involved in aging processes was evaluated in cholangiocytes of young and old mice (2 months and 22 months of age, respectively) and subjected to a model of sclerosing cholangitis. Intracellular pathways that are common to elevated miRs were identified by in silico analysis. Cell proliferation and senescence were evaluated in Twinfilin‐1 ( Twf1 ) knocked‐down cells. In vivo, senescence‐accelerated prone mice ( Samp8, a model for accelerated aging), Twf1 ‐/‐, or their respective controls were subjected to DDC (3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine). Cholangiocytes from DDC‐treated mice showed up‐regulation of a panel of aging‐related miRs . Twf1 was identified by in silico analysis as a common target of the up‐regulated miRs . Twf1 expression was increased both in aged and diseased cholangiocytes, and in human cholangiopathies. Knock‐down of Twf1 in cholangiocytes reduced cell proliferation. Senescence and senescence‐associated secretory phenotype marker expression increased in Twf1 knocked‐down cholangiocytes following pro‐proliferative and pro‐senescent (10‐day lipopolysaccharide) stimulation. In vivo, Samp8 mice showed increased biliary proliferation, fibrosis, and Twf1 protein expression level, whereas Twf1 ‐/‐ had a tendency toward lower biliary proliferation and fibrosis following DDC administration compared with control animals. Conclusion: We identified Twf1 as an important mediator of both cholangiocyte adaptation to aging processes and response to injury. Our data suggest that disease and aging might share common intracellular pathways.